2018
DOI: 10.9734/mrji/2018/41690
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Aetiology and Antibiotic Susceptibility Profile of Post-Operative Sepsis among Surgical Patients in a Tertiary Hospital in Rural Eastern Uganda

Abstract: Background:Post-operative wound sepsis remains a surgical challenge of public health concern constituting approximately 20% of the health care-associated nosocomial infections. This study aimed at determining the prevalence and antimicrobial resistance patterns of bacterial pathogens isolated from post-operative wound infections at Mbale Regional Referral Hospital.Materials and Methods:This was a descriptive cross-sectional study conducted from June to October 2015. Study participant samples were sub-cultured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
12
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 25 publications
(21 reference statements)
7
12
2
Order By: Relevance
“…Findings on the resistance rates of gram negative rods were comparable to the results obtained from a study in Ethiopia [27]. Additionally, MRSA rate of 65.4% observed in the present setting was in harmony with results from a study conducted in Uganda that reported a MRSA rate of 65.9% [28]. These current occurrences were attributed to lack of effective surveillance programs for SSI etiologies and their antibiograms.…”
Section: Discussionsupporting
confidence: 87%
“…Findings on the resistance rates of gram negative rods were comparable to the results obtained from a study in Ethiopia [27]. Additionally, MRSA rate of 65.4% observed in the present setting was in harmony with results from a study conducted in Uganda that reported a MRSA rate of 65.9% [28]. These current occurrences were attributed to lack of effective surveillance programs for SSI etiologies and their antibiograms.…”
Section: Discussionsupporting
confidence: 87%
“…The patient's carried endogenous micro ora may all play a vital role in the cause of nosocomial infections (19) (20). In a study conducted on surgical wound infections in the hospital indicated that 65.9% of the cases were caused by MRSA strains (21).…”
mentioning
confidence: 99%
“…Second, we did not culture the micro-organisms to identify the cause of the SSI. However, other studies in the region have been done and the common organisms that cause SSI and the drug sensitivity pattern have been studied and are now known (Hope et al, 2019) (George et al, 2018).…”
Section: Discussionmentioning
confidence: 99%